Effect of curing conditions on compressive strength of FA-POFA-based geopolymer mortar - Nor Hasanah, Abdul Shukor Lim; Mostafa, Samadi; Nur Farhayu, Ariffin; Mohd Warid, Hussin; Bhutta, M.A.R.; Noor Nabilah, Sarbini; Nur Hafizah, Abd Khalid; Eeydzah, Aminudin (IOP Publishing, 2018)
This paper presents the effect of curing conditions on geopolymer mortar prepared from the blend of palm oil fuel ash (POFA) and fly ash (FA) as full replacement of cement with a combination of sodium silicate and sodium hydroxide solution used as alkaline liquid. The density and strength of the geopolymer mortars with FA:POFA mass ratios of 70:30 together with sodium silicate solution-to-sodium hydroxide solution by mass is 2.5, are investigated. The concentration of alkaline solution used is 14 Molar. Tests were carried out on 70 × 70 × 70 mm cube geopolymer mortar specimens. The effects of curing conditions including the duration of heat curing, temperature of heat curing and delay time before heat curing on compressive strength of mortar are examined. The results revealed that as the temperature increased the compressive strength of geopolymer mortar are increases, the delay time before heat curing increased, the compressive strength of geopolymer mortar reduced and suitable duration for heat curing is within one to two days.